Potential use of nitrate reductase as a biomarker for the identification of active and dormant inhibitors of mycobacterium tuberculosis in a THP1 infection model - Sarkar, Sampa; Sarkar, Dhiman (Journal of Biomolecular Screening, 2012)
The development of a macrophage-based, antitubercular high-throughput screening system could expedite discovery programs for identifying novel inhibitors. In this study, the kinetics of nitrate reduction (NR) by Mycobacterium tuberculosis during growth in Thp1 macrophages was found to be almost parallel to viable bacilli count. NR in the culture medium containing 50 mM of nitrate was found to be optimum on the fifth day after infection with M. tuberculosis. The signal-to-noise (S/N) ratio and Z-factor obtained from this macrophage-based assay were 5.4 and 0.965, respectively, which confirms the robustness of the assay protocol. The protocol was further validated by using standard antitubercular inhibitors such as rifampicin, isoniazid, streptomycin, ethambutol, and pyrazinamide, added at their IC90 value, on the day of infection. These inhibitors were not able to kill the bacilli when added to the culture on the fifth day after infection. Interestingly, pentachlorophenol and rifampicin killed the bacilli immediately after addition on the fifth day of infection. Altogether, this assay protocol using M. tuberculosis-infected Thp-1 macrophages provides a novel, cost-efficient, robust, and easy-to-perform screening platform for the identification of both active and hypoxic stage-specific inhibitors against tuberculosis.
Keywords: high-throughput screening; inhibitor; Mycobacterium tuberculosis; nitrate reductase; THP1

Phytase isozymes from aspergillus niger NCIM 563 under solid state fermentation: biochemical characterization and their correlation with submerged phytases - Bhavsar, Kavita P.; Buddhiwant, Priyanka; Soni, Sarvesh K.; Depan, Dilip; Sarkar, Sampa; Khire, Jayant Malhar (Process Biochemistry, 2013)
Aspergillus niger NCIM 563 produces dissimilar phytase isozymes under solid state and submerged fermentation conditions. Biochemical characterization and applications of phytase Phy III and Phy IV in SSF and their comparison with submerged fermentation Phy I and Phy III were studied. SSF phytases have a higher metabolic potential as compared to SmF. Phy I is tetramer and Phy II, III and IV are monomers. Phy I and IV have pH optima of 2.5 and Phy II and III have pH optima of 5.0 and 5.6, respectively. Phy I, III and IV exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. SSF phytase is less thermostable as compared to SmF phytase. Phy land II show homology with other known phytases while Phy III and IV show no homology with SmF phytases and any other known phytases from the literature suggesting their unique nature. This is the first report about differences among phytase produced under SSF and SmF by A. niger and this study provides basis for explanation of the stability and catalytic differences observed for these enzymes. Exclusive biochemical characteristics and multilevel application of SSF native phytases determine their efficacy and is exceptional. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: A. niger; Isozymes; Phytase; Solid state fermentation; Submerged fermentation